THE SIGNIFICANCE OF ENTREPRENEURSHIP EDUCATION LITERACY IN THE ERA OF DIGITAL TRANSFORMATION: GRADUATES OF THE POSTPANDEMIC COVID-19 UNEMPLOYMENT CRISIS - Irma Wani Othman; Saifulazry Mokhtar; Adelaine Tham; Kelvin Yong (International Journal of Accounting, Finance and Business, 2021)
In the context of Malaysian higher education institutions and in accordance with theIndustrial Revolution 4.0, all corners of the world are predicted to enter the era of mega trendsin which digital transformation pervades all aspects of life, necessitating adaptation by theyounger generation. This paper discusses the general knowledge and understanding ofentrepreneurship education literacy in the digital transformation era. Graduates facing thepost-Pandemic Covid-19 unemployment crisis is the study’s primary focus. The qualitativeresearch methodology used is based on the inaugural background, so this paper puts theresearch lens on a selection of contemporary issues such as emphasis on the university toexpose students to have more than one skill through entrepreneurship education, which refersto (i) soft skills as the basis of economic regeneration, (ii) entrepreneurial skills with theexistence of new opportunities for entrepreneurs, and (iii) relevance of E-commerce with ICTand technical skills of graduates. Meanwhile, collaboration and industry commitment indicateintense cooperation between higher education institutions, thus providing many benefits tograduates, particularly in overcoming Malaysia’s graduate unemployment crisis. Emphasisingthe importance of universities and industry working together to increase employmentopportunities and graduate marketability, among the issues of concern are (i) involvement ofthe industry in HEIs, (ii) CEO@Faculty Programme, and (iii) 2u2i Programme and IndustrialTraining Policy.